Influence of processing parameters on the properties of carbon fibres – an overview: Einfluss der Fertigungsparameter auf die Eigenschaften der Kohlenstofffasern – ein Überblick. Issue 11 (11th November 2016) - Jäger, H.; Cherif, C.; Kirsten, M.; Behnisch, T.; Wolz, D. S.; Böhm, R.; Gude, M.
Abstract : Several studies have shown the importance of carbon fibres (CF) for different high technology markets. In recent years, different fibre types with improved properties have been developed for those markets. Polyacrylonitrile (PAN) copolymers are the basic raw material (precursor) for these fibres in the predominant case. Improvements of the mechanical fibre properties have mainly been achieved by defect reduction during the manufacturing process. Thus, commercial carbon fibres with tensile strengths up to approx. 7000 MPa are currently available. It can be shown that the strengths can be further increased (in the direction of graphene properties) when the relationship between process conditions and defects due to manufacturing of the fibres is better understood. In this context, novel processes like electron beam crosslinking or UV‐activation have proven to be very promising. The article gives an overview about the current situation in the field of carbon fibres development and particularly shows recent shortcomings with respect to novel applications.